Electrochemical Reduction Behaviour of Some Substituted Epoxide - Raveendra Reddy, C.; Jayarama Reddy, S. (Asian Journal of Chemistry, 2010)
The electrochemical reduction behaviour of some substituted epoxides such as 1-(4-methyl)phenyl-3-phenyl-2,3-epoxypropan-1-one, 1-(4-amino) phenyl-3-phenyl 2,3-epoxypropan-1-one and 1-(2,4-dimethoxy)phenyl-3-phenyl-2,3-epoxypropan-1-one has been studied by employing advanced electrochemical techniques such as d.c. polarography, cyclic voltammetry and differential pulse polarography in the universal buffers of pH ranging from 2.0 to 12.0 in DMF-water mixtures. Millicoulometry is employed for the determination of number of electrons involved in the electrode process. Kinetic parameters such as diffusion coefficient and heterogeneous forward rate constant values are evaluated and reported. A reduction mechanism is proposed based on the results obtained. Differential pulse polarography is employed for the quantitative determination of all the three compounds in trace levels using standard addition and calibration methods.